1998
DOI: 10.1021/bc970148g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Conformational Epitope of Hen Egg White Lysozyme by Differential Chemical Modification of Immune Complexes and Mass Spectrometric Peptide Mapping

Abstract: A new approach for the characterization of conformationally dependent epitope structures in protein antigens is described using differential chemical modification of immune complexes in combination with mass spectrometric peptide mapping analysis. Well-established methods for epitope characterization are frequently not applicable to conformationally dependent epitopes, and direct methods of structure analysis such as X-ray crystallography of immune complexes have been successful only in a few cases. Our approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…Affinity mass spectrometry approaches using proteolytic epitope excision and epitope extraction have been previously described in detail and applied in epitope identifications [14][15][16][17][18][19]. In the general analytical method [14][15][16][17]19], the immobilised ligand-binder (antigen-antibody) complex is subjected to limited proteolytic digestion, followed by mass spectrometric analysis of the eluted affinity-bound epitope peptide fragment (s). In the proteolytic step, the epitope is protected from digestion owing to the shielding of the ligand-binder interaction structure; hence, epitope excision on an immobilised immune complex is essential for isolation, specific dissociation and identification of the bound epitope.…”
Section: Introductionmentioning
confidence: 99%
“…Affinity mass spectrometry approaches using proteolytic epitope excision and epitope extraction have been previously described in detail and applied in epitope identifications [14][15][16][17][18][19]. In the general analytical method [14][15][16][17]19], the immobilised ligand-binder (antigen-antibody) complex is subjected to limited proteolytic digestion, followed by mass spectrometric analysis of the eluted affinity-bound epitope peptide fragment (s). In the proteolytic step, the epitope is protected from digestion owing to the shielding of the ligand-binder interaction structure; hence, epitope excision on an immobilised immune complex is essential for isolation, specific dissociation and identification of the bound epitope.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic feature of antigen-antibody complexes has been employed for the development of a general mass spectrometric approach for the identification of protein epitopes, as initially shown by combining limited proteolytic cleavage of intact immune complexes (epitope excision) with mass spectrometric peptide mapping [12]. Whereas initial applications of mass spectrometric epitope mapping have been performed on small sequence epitopes such as from pure polypeptides [15,17,18,19], several recent studies have shown that large, native proteins including conformational epitopes can also be successfully investigated [14,15,20,21,22,23,24,25]. Several bioanalytical applications have ascertained the mass spectrometric epitope mapping/epitope excision approach as a powerful tool; recent examples are the identification of a specific epitope from the Alzheimer's amyloid precursor protein, and the elucidation of an amyloid plaque-specific epitope which directly provides a lead structure for vaccine development against Alzheimer's disease [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Another approach for the characterization of discontinuous epitopes is differential chemical modification of amino acids in the immune complex and in the free Ag. Differences in the reactivity of the same amino acid in the Ab-Ag complex and the free Ag can provide information about the amino acids involved in affinity binding (37).…”
Section: Discussionmentioning
confidence: 99%